Millennials' Purchase Intention Towards Online Travel Agent in Indonesia - Ruth Srininta Tarigan; Jacqueline , (Master of Management, School of Business and Management, Petra Christian University, 2018)
This study investigates the factors that impact Indonesian millennials when purchasing airline tickets through the Online Travel Agent. Millennials’ purchase intention is the focus of this study because millennial is half of Indonesia’s financially strong population and is tech-savvy. Thus this generation is very likely to shop online. Four factors proposed in this study, namely ease of payment, trust, benefits of online shopping, and information quality, were hypothesized to affect millennial's purchasing decision. Data is gathered from millennials who have bought airline tickets online. The questionnaire is spread online, and data from 94 valid respondents is collected. To test the hypotheses, the data is analyzed with Multiple Linear Regression using SPSS. The adjusted r-square result is 0.483, which means that 48.3% of the variability of the dependent variable is explained by the four independent variables. While the t-test result suggests that, out of the four factors previously found to affect purchase intention in general, only three affect millennials’ purchase intention, namely ease of payment, trust, and benefits of online shopping. Information quality is found to have an insignificant effect towards millennials’ purchase intention.